Detecção do vírus da leucose bovina em carcinoma mamário no estado da Paraíba - Fernandes, Igor Cordeiro (2023)
Breast cancer is a heterogeneous and multifactorial disease, in which genetic and environmental factors are involved. Among environmental factors, persistent infections caused by oncoviruses have been related to tumorigenesis and tumor aggressiveness in breast tumors. Studies have demonstrated the presence of the Bovine Leukosis Virus (BLV) genome in samples of human mammary carcinoma. Despite its importance, there is no study of the detection of BLV in breast tumors of patients in the State of Paraíba. Thus, this study aimed to perform the detection of BLV in samples of human breast carcinoma from patients in the State of Paraíba, Northeastern Brazil. BLV screening was performed on 189 paraffin-embedded breast carcinoma samples, including luminal A, luminal B, HER-2, triple negative (TBNC), and super-HER-2 subtypes. For the detection of the viral genome, the techniques of Polymerase Chain Reaction (PCR), Real-Time Quantitative Polymerase Chain Reaction (qPCR), Nested PCR, and Auto-Nested PCR were used. The results of the present study did not show the presence of BLV DNA in any sample of breast carcinoma. Thus, there is no relationship between the presence of BLV and breast carcinoma in the population studied in Paraíba. However, additional studies with a larger number of samples and using other viral genome detection strategies may clarify the role of this virus in mammary carcinogenesis.